FRI0244 MATHEMATICAL PROCESSING IS AFFECTED BY DAILY BUT NOT CUMULATIVE GLUCOCORTOCOID DOSE IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS (SLE). (June 2019) - Mak, Anselm; Teo, Rachel; Kow, Nien Yee; Dhanasekaran, Preeti; Tay, Sen Hee
Abstract : Background: The impact of glucocorticoids on neurocognitive performance in patients with SLE is not fully understood. Objectives: We aimed to study the effect of daily and cumulative doses of glucocorticoids on neurocognitive performance in patients with SLE using the computer-based Automated Neuropsychological Assessment Matric (ANAM). Methods: Consecutive patients with SLE and gender- and age-matched (±5 years) healthy control subject (HC) were studied. In a quiet and comfortable room, each subject underwent the 45-minute ANAM test under supervision which comprises simple reaction time (SRT) that probes neuromuscular efficiency, and 8 domains of neurocognitive assessment including 3 code substitution tests (probing learning and recall), spatial processing (probing visual perception and mental rotation), matching to sample (probing short-term memory and attention), continuous performance test (probing sustained attention), mathematical processing, and memory search (probing working memory). Anxiety and depression were assessed by the Hospital Anxiety and Depression scale (HADS). The total and individual-domain throughput scores (TPS) were compared between both groups using Student's t test. The presence of cognitive dysfunction, defined as total TPS <1.5 SD below the mean TPS of HC, was compared between both groups by χ 2 test. Within the SLE group, the relationships between prednisolone dose (daily [mg] or cumulative [gm]) and individual-domain TPS were first explored by bivariate correlations. Independent association between glucocorticoid dose and individual-domain TPS that showed significant bivariate associations with prednisolone dose was determined by multiple linear regression, with adjustment for potential clinically- and demographically-important cofounders. Results: Ninety-six SLE patients and 96 HC were studied, 16 men (16.7%) were present in each group. The mean age±SD of SLE patients and HC were 36.57±11.4 and 33.61±10.6 years (p=0.073), respectively. The mean±SD duration of SLE, SLEDAI and daily and cumulative prednisolone doses were 98.85±87.4 months, 3.37±3.4, 11.01±13.6mg and 16.92±18.5gm, respectively. SLE patients had a significantly higher mean HADS-anxiety score than HC (6.25±3.3 vs 4.62±3.0, p=0.001) while the mean HADS-depression score was comparable between both groups (p=0.093). SLE patients had significantly shorter duration of education (12.92±3.92 vs 15.86±2.5 years, p<0.001), scored significantly worse across all the 8 ANAM domains, had a significantly lower mean total TPS [337.23±94.4 vs 395.62±87.6, p<0.001) and were significantly more prevalent of cognitive dysfunction as compared to HC (25.0% vs 7.3%, p=0.001). In SLE patients, a statistically significant negative correlation was found between daily prednisolone dose and TPS of mathematical processing (r=-0.248, p<0.015), while no significant correlation between cumulative glucocorticoid dose and any of the individual ANAM domain was found. In multivariate regression, daily prednisolone dose remained independently associated with lower TPS of mathematical processing (β=-0.208, p=0.024) after adjusting for age, gender, SLEDAI, total HADS, total TPS, serum albumin and 25-OH hydroxyvitamin D levels and duration of education in SLE patients. Conclusion: Daily, but not cumulative glucocorticoid dose has an independent impact on the working memory of SLE patients. While how daily glucocorticoid dose affects working memory mechanistically requires further investigation, its impact on neurocognitive assessment in SLE patients cannot be underestimated. Disclosure of Interests: None declared